PENGARUH SERVICE QUALITY, PERCEIVED VALUE, CUSTOMER SATISFACTION TERHADAP POST-PURCHASE INTENTION PADA APPLE DI INDONESIA [THE EFFECT OF SERVICE QUALITY, PERCEIVED VALUE, CUSTOMER SATISFACTION ON POST-PURCHASE INTENTION FOR APPLE IN INDONESIA] - Reynaldi Reynaldi; Dewi Wuisan (Universitas Pelita Harapan, 2023)
This study aims to examine the positive influence of service quality, perceived value, customer satisfaction on post-purchase intention at Apple in Indonesia. As we know, technological developments experience very rapid development every year and affect the tendency of the Indonesian people to access advances in technology, information and communication that require a supporting tool/device such as a smartphone. People use smartphones not only as a means of communication but also as a social and work need. Apple, which is a well-known brand in the smartphone industry, only controlled less than 10% of the smartphone market share in Indonesia in the period August 2019–August 2020. Even though, when viewed from a global growth perspective, the Apple brand has quite high growth compared to its competitors. This is what triggers research on the effect of service quality, perceived value, customer satisfaction on post-purchase intention on Apple products in Indonesia. In this study the sampling technique used was a non-probability sampling technique, namely purposive sampling where the respondents were users of Apple products, located in JABODETABEK and outside JABODETABEK. The sample in this study amounted to 200 respondents with a data collection method in the form of questionnaires distributed via Google Forms. The results of the data obtained were processed using validity, reliability and statistical analysis. Meanwhile, data processing uses Partial Least Square - Structural Equation Modeling (PLS-SEM) processed using SmartPLS 3.0 software. The research results obtained indicate that service quality has a significant positive effect both directly and indirectly on post-purchase intention. Perceived value also has a significant positive effect both directly and indirectly on post-purchase intention. And finally, customer satisfaction has a direct positive effect on Apple's post-purchase intention in Indonesia.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk menguji pengaruh positif service quality, perceived value, customer satisfaction terhadap post-purchase intention pada Apple di Indonesia. Seperti yang kita ketahui bahwa perkembangan teknologi setiap tahunnya mengalami perkembangan yang sangat pesat dan memengaruhi kecenderungan masyarakat Indonesia untuk mengakses kemajuan teknologi, informasi, dan komunikasi yang membutuhkan sebuah alat/device yang menunjang seperti smartphone. Orang-orang menggunakan smartphone tidak hanya sebagai alat komunikasi saja tetapi juga merupakan sebuah kebutuhan sosial dan pekerjaan. Apple yang merupakan sebuah brand yang terkenal di industri smartphone hanya menguasai kurang dari 10% pangsa pasar smartphone di Indonesia pada periode Agustus 2019–Agustus 2020. Padahal apabila dilihat dari segi pertumbuhan global, brand Apple memiliki pertumbuhan yang cukup tinggi dibandingkan pesaingnya. Hal inilah yang memicu untuk dilakukan penelitian mengenai pengaruh service quality, perceived value, customer satisfaction, terhadap post-purchase intention pada produk Apple di Indonesia. Dalam penelitian ini teknik pengambilan sampel yang digunakan adalah teknik non-probability sampling yaitu purposive sampling di mana responden merupakan pengguna produk Apple, yang berada di JABODETABEK dan luar JABODETABEK. Sampel dalam penelitian ini berjumlah 200 responden dengan metode pengumpulan data berupa kuesioner yang disebar melalui Google Forms. Hasil data yang diperoleh diolah dengan menggunakan analisis validitas, reliabilitas, dan analisis statistik. Adapun pengolahan data menggunakan Partial Least Square - Structural Equation Modeling (PLS-SEM) diolah menggunakan software SmartPLS 3.0. Hasil penelitian yang diperoleh menunjukkan bahwa service quality memiliki pengaruh positif signifikan baik secara langsung maupun tidak langsung terhadap post-purchase intention. Perceived value juga memiliki pengaruh positif signifikan baik secara langsung maupun tidak langsung terhadap post-purchase intention. Dan yang terakhir customer satisfaction memiliki pengaruh positif secara langsung terhadap post-purchase intention Apple di Indonesia.